IMPLEMENTASI MANAJEMEN SUMBER DAYA MANUSIA DALAM MENINGKATKAN MUTU PENDIDIKAN DI SEKOLAH MENENGAH KEJURUAN AL-FAQIH SUMBER NYAMPLONG PAMEKASAN - Nasrullah , Ach.; Muchlis Solichin, Mohammad (re-JIEM (Research Journal of Islamic Education Management), 2021)
This study aims to determine the implementation of human resource management in improving the quality of education and the factors that support the implementation of human resource management in improving the quality of education. This research was conducted at SMK Al-Faqih Sumber Nyamplong Kowel Pamekasan using a descriptive qualitative approach. The results of this study indicate that the implementation of Human Resource Management to Improve Education Quality has several stages including a) needs and information analysis, b) teacher recruitment, c) induction of new employees, d) teacher placement, e) granting authority and responsibility for staff, f) implementation of supervision, g) fostering teacher welfare, h) career development for employees, i) termination of relations, and j) severance pay. While the Supporting Factors are a) principals have many considerations, b) programs run in schools can bring positive changes and impacts, c) facilities and infrastructure can be utilized optimally, and d) evaluation.